Princípios ambientais e sua relação com o mandato cultural expresso em Gênesis 1.26-31 e Gênesis 2.5-8 - João Rodrigues, Stélio (Vox Scripturae - Revista Teológica Internacional, 2012)
Understand the relationship between the Creator’s God and his creation is a challenge that gives us a approximation with him. This research proposes to understand the rule given by God in Genesis 1.26-31 e 2.5-8. In this perspective, how does the Christian community assumes the environmental principles into their preaching? It is necessary to highlight points of analogy between the environmental and the Genesis’s biblical texts to Christian preaching. Analyze the environmental principles and their relationship with Genesis 1.26-31 and 2.5-8 for understanding of the values inherent in the relationship creator and creature. Know the environmental principles that are highlighted in the reports of Genesis and its importance in the Christian community. This research presents as an organization: an introduction; two chapters that contains the theory; final considerations and bibliography. In the first chapter describes about ecology highlighting environmental concepts, principles as Conference Rio-92. In the second chapter talks about Genesis 1.26-31 and 2.5-8, called cultural mandate, its definition, focusing too on the relationship of God with his creation. The search ends with the final considerations, that are the synthesis of the work. The texts show that sin behind the remoteness of the man in the presence of God and consequently the depletion and devastation of the environment, contrary to the order given by the creator to have domain creation, responsibly turning their eyes to the creator
Keywords: cultural mandate; ecology; Genesis; Creator